The Impact of Poor Nutrient Intakes and Food Insecurity on the Psychological Distress among Community-Dwelling Middle-Aged and Older Adults during the COVID-19 Pandemic - Malek Rivan, Nurul Fatin (Nutrients, 2021)
This study aimed to investigate the impact of food insecurity and poor nutrient intake on the psychological health of middle-aged and older adults during the COVID-19 pandemic. A sub-sample of 535 individuals aged 52 years and above, from the earlier cohort and interventional studies (n = 4) from four selected states in Peninsular Malaysia, were recruited during the COVID-19 outbreak (April to June 2020). Telephone interviews were conducted by trained interviewers with a health sciences background to obtain participants’ information on health status, physical activity, food security, and psychological health (General Health Questionnaire-12; normal and psychological distress). Univariate analyses were performed for each variable, followed by a logistic regression analysis using SPSS Statistics version 25.0. Results revealed food insecurity (OR = 17.06, 95% CI: 8.24–35.32, p < 0.001), low protein (OR = 0.981, 95% CI: 0.965–0.998, p < 0.05), and fiber intakes (OR = 0.822, 95% CI: 0.695–0.972, p < 0.05) were found to be significant factors associated with the psychological distress group after adjusting for confounding factors. The findings suggested that food insecurity and insufficiencies of protein and fiber intakes heightened the psychological distress during the COVID-19 pandemic. Optimal nutrition is vital to ensure the physical and psychological health of the older population, specifically during the current pandemic.